Rosalía de Castro, Manuel Murguía, their daughter Aura and the revolutionary context of 1968 - Garcia Vega, Lucía (Madrygal. Revista de Estudios Gallegos, 2012)
This research aims to fill some information gaps delayed since the second half of the twentieth century and found to be key studies on the life and literary of Rosalía de Castro (1837-1885), while you are granted a necessary attention to the political context in which it moved her husband, Manuel Martínez Murguía (1833-1923), in the symbolic year 1868.